Stabilisation of atherosclerotic plaques - Ylä-Herttuala, Seppo; Bentzon, Jacob Fog; Daemen, Mat; Falk, Erling; Garcia-Garcia, Hector M.; Herrmann, Joerg; Hoefer, Imo; Jukema, J. Wouter; Krams, Rob; Kwak, Brenda R.; Marx, Nikolaus; Naruszewicz, Marek; Newby, Andrew; Pasterkamp, Gerard; Serruys, Patrick W. J. C.; Waltenberger, Johannes; Weber, Christian; Tokgözoglu, Lale (Thrombosis and Haemostasis, 2011)
Plaque rupture and subsequent thrombotic occlusion of the coronary artery account for as many as three quarters of myocardial infarctions. The concept of plaque stabilisation emerged about 20 years ago to explain the discrepancy between the reduction of cardiovascular events in patients receiving lipid lowering therapy and the small decrease seen in angiographic evaluation of atherosclerosis. Since then, the concept of a vulnerable plaque has received a lot of attention in basic and clinical research leading to a better understanding of the pathophysiology of the vulnerable plaque and acute coronary syndromes. From pathological and clinical observations, plaques that have recently ruptured have thin fibrous caps, large lipid cores, exhibit outward remodelling and invasion by vasa vasorum. Ruptured plaques are also focally inflamed and this may be a common denominator of the other pathological features. Plaques with similar characteristics, but which have not yet ruptured, are believed to be vulnerable to rupture. Experimental studies strongly support the validity of anti-inflammatory approaches to promote plaque stability. Unfortunately, reliable non-invasive methods for imaging and detection of such plaques are not yet readily available. There is a strong biological basis and supportive clinical evidence that low-density lipoprotein lowering with statins is useful for the stabilisation of vulnerable plaques. There is also some clinical evidence for the usefulness of antiplatelet agents, beta blockers and renin-angiotensin-aldosterone system inhibitors for plaque stabilisation. Determining the causes of plaque rupture and designing diagnostics and interventions to prevent them are urgent priorities for current basic and clinical research in cardiovascular area.
Keywords: Atherosclerosis; imaging; plaque stabilisation; treatment; vulnerable plaques